A Review about Geographical Theory and the Main Conceptions in Human Geography: - (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Since geography is a science of several methods, staying in the crossroad of different sciences, needed techniques from several other related areas. For the one side, it's situated among natural sciences or the planet earth, from geology to biology and meteorology, and also on the opposite side, amongst the social sciences, from history to sociology and economic system. It's because of this that geographers are continually discussing all about the objectives, unity as well as techniques of geography. Nevertheless, the unity can't be methodological since it uses the techniques of social and natural sciences. This particular variability of orientations helps it be a science really smart to conjectural issues in relation to the demand of worldwide knowledge inherent to interpersonal worries.